Case Report: Let Us Not Forget the Treatment That Some Patients Have Received—The Brief 50-Year History of a Kidney Transplant Survivor - Nordheim, Espen; Raki, Melinda; Midtvedt, Karsten (Frontiers in Medicine, 2022)
Background There has been a considerable improvement in post-transplant care since the early 1960s. Some patients we meet in the clinic have personally experienced this progress and have histories to tell that one must not forget. This is the brief history of a long-time “transplant survivor.” Case Presentation In 1970, a young woman developed acute oedema, proteinuria, hypertension and oliguria during pregnancy. Labor was induced, but neither the child nor the kidney function could be saved. Our patient started dialysis, and 4 years later received a kidney transplant donated by her father (then 55 years of age). Maintenance immunosuppression consisted of prednisolone and azathioprine until 2011, when azathioprine was switched to everolimus due to skin cancer. Before this, our patient was highly satisfied with prednisolone/azathioprine, despite discussions regarding newer immunosuppressive drugs, and always reminded the treating physician that one should “never change a winning team.” Retrospectively, the avoidance of calcineurin inhibitors might have been beneficial for this patient who still has preserved an excellent renal function with s-creatinine levels around 100 μmol/L and just had sparse fibrosis detected in a recently performed transplant biopsy. The transplanted kidney is now 101 years old and is still working 24/7. Conclusions Our patient received a kidney transplant for 46 years ago and still has a remarkably stable transplant function with s-creatinine levels around 100 μmol/L. This case report illustrates the potential endurance of the kidneys and is a reminder to keep taking individualized treatment decisions even though new treatment alternatives promise superiority.